Multi-state and Interleaved Converters With Passive Impedances for Current Sharing - Bascopé, René P. T.; Bascopé, Grover V. T.; Brito Jr., Francisco J. B.; Daher, Sérgio (Eletrônica de Potência, 2014)
This paper presents multilevel switching cells that allow the generation of high-power nonisolated dc-dc, ac-dc, dc-ac, and ac- ac converters. The cells are classified in two groups: multi-state switching cells (MSSC) based on autotransformer and interleaved switching cells (ISC) based on inductors. Each switching cell has an impedance based on a small inductor Lsh connected between the legs, which is named current sharing circuit (CSC) and guarantees zero average voltage across the involved magnetic components, therefore compensating eventual differences between the PWM (pulse width modulation) duty cycles. The small inductor causes the duty cycle to be reduced, and consequently its inductance is typically very small. In order to verify the current sharing between the magnetic components, two dc-dc buck converters operating at 25 kHz and rated at 1 kW, where the input voltage is 200 V and the output voltage is 60 V , are implemented and evaluated in laboratory.